Ultrasmooth organic-inorganic perovskite thin-film formation and crystallization for efficient planar heterojunction solar cells. - Zhang, W; Saliba, M; Moore, D; Pathak, S; Hörantner, M; Stergiopoulos, T; Stranks, S; Eperon, G; Alexander-Webber, J; Abate, A; Sadhanala, A; Yao, S; et al. (Nature Publishing Group, 2015)
To date, there have been a plethora of reports on different means to fabricate organic-inorganic metal halide perovskite thin films; however, the inorganic starting materials have been limited to halide-based anions. Here we study the role of the anions in the perovskite solution and their influence upon perovskite crystal growth, film formation and device performance. We find that by using a non-halide lead source (lead acetate) instead of lead chloride or iodide, the perovskite crystal growth is much faster, which allows us to obtain ultrasmooth and almost pinhole-free perovskite films by a simple one-step solution coating with only a few minutes annealing. This synthesis leads to improved device performance in planar heterojunction architectures and answers a critical question as to the role of the anion and excess organic component during crystallization. Our work paves the way to tune the crystal growth kinetics by simple chemistry.